PEMANTAPAN MATERI KERAJAAN SINGHASARI BAGI MGMP SEJARAH SMA DAN SMK JAWA TIMUR SEBAGAI UPAYA MEMPERKENALKAN TEMUAN MUTAKHIR - Wahyudi, Deny Yudo (Bhakti: Jurnal Pengabdian Masyarakat, 2025)
It is essential for teachers, especially history teachers, to possess strong professional competencies, as the outcomes or objectives of history education are closely related to the orientation of learning that focuses on the transfer of values based on various historical facts obtained through research using scientific methods (both historical and archaeological research methods). The need or obligation to continuously develop professional competence requires history teachers in East Java to stay up to date with the latest historical research findings to ensure the development of high-quality teaching materials that align with scientific advancements. More specifically, there is a need for a platform that enables history teachers in East Java to gain an optimal understanding of the latest research findings related to the Singhasari Kingdom, a kingdom that played a crucial role in the formation of Indonesia. Consequently, it has become an important topic that must be taught in history lessons at Phase E, in accordance with the Learning Outcomes for History as stated in the Merdeka Curriculum. This community service program was carried out through several stages, namely: situation analysis, activity recommendations, curriculum and module design, preparation of learning materials on the Singhasari Kingdom, implementation, program evaluation, and follow-up planning. If teachers are able to optimize the use of various resources around them, the implementation of history learning using approaches that are relevant to students’ conditions and needs—such as the contextual approach—can also be effectively realized. This aligns with the materials presented by the resource person regarding the latest findings related to the Singhasari Kingdom.